FIB analysis of fossils plant remains: Technical and experimental aspects - Benedetti, Alessandro (2018)
We present a comprehensive study about the technical aspects of the application of focused ion beam (FIB) to thestudy of cuticles and compressions of fossil leaves.The technique allowed us to cross section and image fossil coalified plant remains with a spatial resolution withinthe 10 nm range, far higher than any other method employed so far.At various stages of the milling process, we observed significant gallium redeposition on the trench walls, particularly pronounced in the case of cavities. These highly unwanted artefacts can be greatly reduced, but not wholly eliminated, by lowering either or both the beam current and acceleration voltage; nevertheless, great care is needed when interpreting cross-sectional images.